Establishment of share unit formula for strata residential buildings and its implication to buyer and unit owner - Md Zana, Rubiah; Siti Nur Alia Roslan, Dr; KhairulFaizah Mustafa, Nur; Senawi, Asma (International Journal of Engineering and Technology, 2018)
Stratified development has become a trend nowadays and still expanding to suit with the scarcity of land. During the implementation of the early Strata Titles Act, there are many issues and disputes raised in terms of its legislation, rule and regulation, implementation, management and maintenance. One of the issues is the establishment and implementation of share unit formula to strata building. Recently, the government of Malaysia has formulated and approved the new Act which is called the Strata Management Act 2013 whereby several amendment has been made to strengthen and improve the current exercise and give a new breath to strata building development. The objective of this paper is to study the establishment of Share Unit Formula for strata residential building in Klang Valley and the implication of the new provision to house buyers and unit owners. A quantitative survey has been done by conducting interviews with the professionals in the industry. The findings of the research revealed that there are many advantages obtained by the house buyers and unit owners due to the latest enforcement. Besides promotes transparency and accountability in the housing development industry, it is also help to encourage an efficient application of simultaneous vacant possession of Strata Title to the unit buyers.Â Â